2019
DOI: 10.1017/s1431927619004720
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Humic Acid from Natural Water by ZVI/H2O2 Process

Abstract: Humic acid (HA), a representative fraction of the natural organic matter derived from vegetation and commonly present in natural waters, can contribute to the formation of disinfection by-products when reacting with chlorine during potable water production. These by-products may cause increased risk of cancer, especially in the bladder, and adverse reproductive outcomes [1]. Therefore, identification and removal of organic matter before the chlorination step is required to avoid or minimize the risk of formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…SEM secondary electron-SE images of Figures 2b, 2c, and 2d show heterogeneous oxides morphologies produced on the electrode surface during the EF reaction. It is pertinent to observe here that some similar oxide morphologies formed on the steel surface after an oxidative system using H2O2 but without applied current have been reposted [4]. From this oxidative stage confirmed in the present work, in which the electrode surface was entirely oxidized, satisfactory rates of removal of the target pollutant were obtained: 82% DOC, 99% LC measured as Abs280, and 99% color removal [5].…”
supporting
confidence: 71%
“…SEM secondary electron-SE images of Figures 2b, 2c, and 2d show heterogeneous oxides morphologies produced on the electrode surface during the EF reaction. It is pertinent to observe here that some similar oxide morphologies formed on the steel surface after an oxidative system using H2O2 but without applied current have been reposted [4]. From this oxidative stage confirmed in the present work, in which the electrode surface was entirely oxidized, satisfactory rates of removal of the target pollutant were obtained: 82% DOC, 99% LC measured as Abs280, and 99% color removal [5].…”
supporting
confidence: 71%
“…In recent years, alternatives to soluble iron salts in the Fenton process have been investigated, mainly aimed at the use of solid elemental iron (Fe 0 /ZVI) as this is an efficient electron donor [26,27]. However, the disadvantages of removing metalic iron in the form of particulate powder during and at the end of the treatment have driven interest to a search for other forms of ZVI [27][28][29][30][31][32][33][34][35][36] which may allow easier separation from the water. Among these studies, similar rates of TOC removal have been reported when using ZVI in less conventional forms (such as metal shavings) compared to commercial particulate ZVI powder [36].…”
Section: Introductionmentioning
confidence: 99%